Health Psychology Approaches to Improving Treatment Adherence Among Patients with Chronic Illnesses - Dirga, Afika; Muhktar, Nana; Permata, Indah (Magenta Journal De Healthymedi, 2025)
This study examines health psychology approaches to improving treatment adherence among patients with chronic illnesses, including diabetes mellitus, hypertension, cardiovascular disease, and chronic kidney disease. The research aims to explore how psychological, emotional, social, and cultural factors influence adherence behavior and how patients experience health psychology-based interventions within chronic illness management. A qualitative research design was employed using semi-structured interviews with 25 purposively selected participants undergoing long-term treatment. Data were analyzed through thematic analysis supported by NVivo software to identify recurring themes and patterns related to adherence behavior. The findings indicate that treatment adherence is strongly influenced by illness perception, self-efficacy, emotional well-being, coping strategies, family support, and cultural beliefs. Counseling, motivational interviewing, and patient-centered educational approaches were perceived as effective in strengthening treatment commitment and improving patients’ confidence in managing chronic conditions. The novelty of this study lies in its integrative qualitative exploration of adherence as a multidimensional behavioral process shaped by interconnected psychological and sociocultural experiences. The study implies that healthcare systems should adopt holistic, culturally sensitive, and psychologically informed interventions to improve long-term treatment adherence and patient well-being.